CRISPR-Cas Systems in the Fight Against Antimicrobial Resistance: Current Status, Potentials, and Future Directions - Ahmed MM; Kayode HH; Okesanya OJ; Ukoaka BM; Eshun G; Mourid MR; Adigun OA; Ogaya JB; Mohamed ZO; Lucero-Prisno III DE (Infection and Drug Resistance)
Mohamed Mustaf Ahmed,1,2 Hassan Hakeem Kayode,3 Olalekan John Okesanya,4 Bonaventure Michael Ukoaka,5 Gilbert Eshun,6,7 Marina Ramzy Mourid,8 Olaniyi Abideen Adigun,9 Jerico Bautista Ogaya,10,11 Zeinab Omar Mohamed,1 Don Eliseo Lucero-Prisno III12– 14 1Faculty of Medicine and Health Sciences, SIMAD University, Mogadishu, Somalia; 2Institute for Global Health, SIMAD University, Mogadishu, Somalia; 3Department of Medical Laboratory Science, Oyo State Hospital Management Board, Oyo, Nigeria; 4Faculty of Medicine, Department of Public Health and Maritime Transport, University of Thessaly, Volos, Greece; 5Community and Clinical Research Division, First on-Call Initiative, Port Harcourt, Nigeria; 6Department of Medicine, Seventh Day Adventist Hospital, Asamang, Ghana; 7The Royal (Dick) School of Veterinary Studies and the Roslin Institute, University of Edinburgh, Midlothian, UK; 8Faculty of Medicine, Alexandria University, Alexandria, Egypt; 9Department of Medical Laboratory Science, Nigerian Defence Academy, Kaduna, Kaduna State, Nigeria; 10Department of Medical Technology, Institute of Health Sciences and Nursing, Far Eastern University, Manila, Philippines; 11Center for University Research, University of Makati, Makati City, Philippines; 12Department of Global Health and Development, London School of Hygiene and Tropical Medicine, London, UK; 13Research and Innovation Office, Southern Leyte State University, Sogod, Leyte, Philippines; 14Research and Development Office, Biliran Province State University, Naval, Biliran, PhilippinesCorrespondence: Mohamed Mustaf Ahmed, Email momustafahmed@simad.edu.soBackground: Antimicrobial resistance (AMR) is a critical global health concern that threatens the efficacy of existing antibiotics and poses significant challenges to public health and the economy worldwide. This review explores the potential of CRISPR-Cas systems as a novel approach to combating AMR and examines current applications, limitations, and prospects.Methods: A comprehensive literature search was conducted across multiple databases, including PubMed, Google Scholar, Scopus, and Web of Science, covering publications published from 2014 to August 2024. This review focuses on CRISPR-Cas technologies and their applications in AMR.Results: CRISPR-Cas systems have demonstrated efficacy in combating antimicrobial resistance by targeting and eliminating antibiotic-resistance genes. For example, studies have shown that CRISPR-Cas9 can effectively target and eliminate colistin resistance genes in MCR-1 plasmids, restoring susceptibility to carbapenems in bacteria such as E. coli and Klebsiella pneumoniae. Further molecular findings highlight the impact of CRISPR-Cas systems on various bacterial species, such as Enterococcus faecalis, in which CRISPR systems play a crucial role in preventing the acquisition of resistance genes. The effectiveness of CRISPR-Cas in targeting these genes varies due to differences in CRISPR locus formation among bacterial species. For instance, variations in CRISPR loci influence the targeting of resistance genes in E. faecalis, and CRISPR-Cas9 successfully reduces resistance by targeting genes such as tetM and ermB.Conclusion: CRISPR-Cas systems are promising for fighting AMR by targeting and eliminating antibiotic-resistant genes, as demonstrated by the effective targeting of colistin resistance genes on MCR-1 plasmids and their similar activities. However, the effectiveness of CRISPR-Cas is affected by variations in the CRISPR loci among bacterial species. Challenges persist, such as optimizing delivery methods and addressing off-target effects to ensure the safety and precision of CRISPR-Cas systems in clinical settings.Keywords: CRISPR-Cas systems, antimicrobial resistance, gene editing, bacteriophage delivery